EFEK PROTEKSI DEKOKTA KULIT ALPUKAT PADA HEPAR TIKUS TERINDUKSI KARBON TETRAKLORIDA - Phebe Hendra; Paramita Liong; Brigita Wina Rosari Putri; Angeline Syahputri Fransiskus; Fransisca Andriani; Asih Putriati; Theresia Eviani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
The decoction of avocado peels was tested for their hepatoprotective activity against carbon tetrachloride-induced hepatotoxicity in rat. The rats were treated with the decoction of avocado peels at doses of 363; 762, 1600 mg/kg per oral once in a day for 6 days and carbon tetrachloride (2 mL/kg) was given on the 7th day. Different groups of rats were given water decoction of avocado peels at a dose of 363; 762, 1600 mg/kg and after 6 hours received carbon tetrachloride (2 mL/kg), respectively. The degree of protection was measured by using biochemical parameters like serum transaminase, alkaline phosphatase and albumin. From these results it suggested that the decoction of avocado peels 762, 1600 mg/kg for 6 hours has a potent hepatoprotective action upon carbon tetrachloride-induced hepatic damage in rats.